THE INFLUENCE OF THE KOREAN WAVE AND EVENT MARKETING ON PURCHASING DECISIONS SEVENTEEN MERCHANDISE (STUDY ON FOLLOWERS OF THE X ACCOUNT @CARATSTALK) - Arief Budiyanto; Ela Minulyawati (International Journal Multidisciplinary Science, 2024)
This research aims to determine the influence of Korea Wave/Hallyu (Korean Wave) and Event Marketing (Marketing Events) on Purchase Decisions for Seventeen merchandise among followers of the X @caratstalk account. The method used is quantitative. A total of 96 people were used as respondents in the research. Data analysis uses regression with SPSS 25.0 as an analysis tool. The results of this research show that the Korean Wave has a significant influence on purchasing decisions. The t hypothesis test proves this, obtained count> table or (3.067 > 1.985). And Event Marketing influences purchasing decisions. The value of count proves this> table (5.650 > 1.985). Korea Wave and Event Marketing have a significant influence on Purchasing Decisions. This is proven by Fcount > Ftable or (58.432 > 3.09)